Using a virtual learning environment to address one problem with problem based learning. - Ward K; Hartley J (Nurse Education in Practice, 2006)
A successful problem based learning approach to the education of health care professionals is dependent upon facilitators having access to a bank of authentic scenario. The assertion made here is that methods employed to build scenario, containing problems that act as triggers for learning, are difficult to author and compel the facilitator to define the problems at the outset negating any need for the learner to engage in problem identification, a crucial skill for learners to acquire. The article explores several methods of building scenario that have the potential to offer a solution to the problem of problem pre-definition with the conclusion that they all have limitations and bring with them a new set of challenges for the facilitator. The article goes on to introduce Penfield Virtual Hospital (Penfield), a computer-based tool developed to address some of the challenges posed by scenario building particularly relating to problem pre-definition.